A randomised trial of granulocyte-macrophage colony-stimulating factor for neonatal sepsis: outcomes at 2 years. Issue 1 (27th April 2012) - Marlow, Neil; Morris, Timothy; Brocklehurst, Peter; Carr, Robert; Cowan, Frances M; Patel, Nishma; Petrou, Stavros; Redshaw, Maggie E; Modi, Neena; Dore, Caroline
Abstract : Objective: The authors performed a randomised trial in very preterm small-for-gestational age (SGA) babies to determine if prophylaxis with granulocyte-macrophage colony-stimulating factor (GM-CSF) improves outcomes (the PROGRAMS trial). Despite increased neutrophil counts following GM-CSF, the authors reported no significant difference in neonatal sepsis-free survival. Patients and methods: 280 babies born <31 weeks of gestation and SGA were entered into the trial. Outcome was determined at 2 years to determine neurodevelopmental and general health outcomes, including economic costs. Results: The authors found no significant differences in health outcomes or health and social care costs between the trial groups. In the GM-CSF arm, 87 of 134 (65%) babies survived to 2 years without severe disability compared with 87 of 131 (66%) controls (RR: 1·0, 95% CI 0·8 to 1·2). Marginally, more children receiving GM-CSF were reported to have cough (RR 1·7, 95% CI 1·1 to 2·6) and had signs of chronic respiratory disease (Harrison's sulcus; RR 2·0, 95% CI 1·0 to 3·9) though this was not reflected in bronchodilator use or need for hospitalisation for respiratory disease. Overall, the rate of neurologic abnormality (7%–9%) was similar but mean overall developmental scores were lower than expected for gestational age. Conclusions: The administration of GM-CSF to very preterm SGA babies is not associated with improved or more adverse outcomes at 2 years of age. The apparent excess of developmental impairment in the entire PROGRAMS cohort, without corresponding increase in neurological abnormality, may represent diffuse brain injury attributable to intrauterine growth restriction.